Using the jar model to improve students’ understanding of operations on integers - Badarudin, Bny Rosmah; Khalid, Madihah (Belgium Printing, 2008)
The focus of this paper is to report on a study that assess students’ knowledge and understanding of integers before and after the invention teaching using the ‘jar model’. The paper will concentrate on the kind of errors students make in learning integers and how the ‘jar model’ was supposed to enhance students’ understanding instead of memorizing rules like ‘negative times negative gives positive’ etc. Analyses from interviews and performance data of the pre and post-intervention stage revealed that most of the students can understand the jar model and thus improvement can be seen from the result of the post-test.